The Role of Customer Relationship Management in Indonesia Business - Erna Andajani; Nurul Badriyah (University of Islam Malang, 2017)
Companies need to have tactics to win business competition. One way that can be used by the company is to recognize and understand the customer. Companies that perform customer relationship management will be able to sustain its business. The existence of customers is the driving force of business enterprises in various industries. In business services, the customer can be as an actor and a very crucial business objects. This study aimed to clarify the concept of customer relationship management and serves some research management customer relations in Indonesia. The study also describes the application of customer relationship management the company has done in Indonesia.Â Â Keywords : Customer Relationship Management, Customer, Relationship Judul Asli : Peran Manajemen Hubungan Pelanggan dalam Bisnis Indonesia